LARVICIDAL EFFICACY OF MEDICINAL PLANT EXTRACTS FOR THE CONTROL OF MOSQUITOE VECTORS - RAVICHANDRAN RAMANIBAI,; KANAYAIRAM VELAYUTHAM, (International Journal of Pharma and Bio Sciences, 2014)
The larvicidal activities to determine the efficacies of acetone, ethyl acetate, chloroform and butanol dried leaf extracts of Annona squamosa, Cynodon dactylon, Melia azedarach and root extract of Hemidesmus indicus tested against 3rd instar Culex quinquefasciatus and Aedes aegypti. The highest larvae mortality was found in the acetone followed by ethyl acetate, chloroform and butanol extract of A. squamosa with LC50 values of 594.60, 490.35, 143.90, 117.98 and 280.62, 343.89, 156.92, 471.94 ppm; C. dactylon with LC50 values of 585.86, 143.32, 74.33, 148.65 and 408.48, 198.43, 169.28, 385.55 ppm; M. azedarach with LC50 values of 264.87, 65.27, 88.39, 514.65 and 192.78, 148.65, 172.24, 235.97 ppm H. indicus with LC50 values of 210.22, 174.82, 117.98, 445.45 and 363.91, 255.47, 186.61, 338.56 ppm against C. quinquefasciatus and A. aegypti. Our result suggested that the ethyl acetate of M. azedarach leaf extract was an excellent larvicidal potential in controlling filariasis and dengue vectors.